Study of Lip Print Pattern among Young Individuals in Bangalore City (Indian Journal of Forensic Medicine & Toxicology, 2020)
Chieloscopy or study of pattern of lip print is one of the easiest tools available for the identification of anindividual in a medico legal investigation. The present study involves evaluating the pattern of lip printsamong hundred individuals with 50 male and 50 female subjects. Lip prints are obtained on a white bondpaper and studied involving all four quadrants. It was observed that Type I pattern was commonest lip printpattern among all the individuals and in female subjects, where as type II pattern was common among males.No two individuals had the same lip print pattern.